Perlindungan Hukum Terhadap Korban Tindak Pidana Penipuan Melalui Sosial Media Di Kabupaten Kepulauan Aru: - Ingkeatubun, Yohanes Fendy Armando; Rosando, Abraham Ferry (Harmonization : Jurnal Ilmu Sosial, Ilmu Hukum, dan Ilmu Ekonomi, 2024)
Criminality in cyberspace, especially a fraud from social media is one of a lot of kind of criminality mode which happening so often. The effortts thats has been taken from the polise of Kepulauan Aru in this case is a preventive and represive action to delve the way and the cause of this kind of criminality. There is a lot of things that supportless like the unperfect facilities so is its hard for the police to solve thing up. Because of that, there’s still needed a support in the facilities thing from the local government for the police of Kabupaten Kepulauan Aru so they can solve this cyber crime cases up. The research method carried out is normative legal research which focuses on the provisions of the applicable legislation. And also legal opinions obtained through books, papers, research results, the internet, opinions of legal scholars, practical law and relevant newspapers along with the Big Indonesian Dictionary and Legal Dictionary, after which it will be collected and processed using the Legal Reasoning method and then clarified and analyzed using sources that have been analyzed systematically. The forms of legal protection for victims are the provision of restitution and compensation, counseling, legal assistance, provision of information and there are many more that can be given to victims because victims (society) are very weak individuals before the law. The form of action taken against the perpetrators of fraud through social media by tracking the social media accounts used by the perpetrators in carrying out their actions and finding out the whereabouts of the perpetrators to find the perpetrators so that applicable penalties can be applied.